Reduced-dose C-arm computed tomography applications at a pediatric institution - Acord, Michael; Shellikeri, Sphoorti; Vatsky, Seth; Srinivasan, Abhay; Krishnamurthy, Ganesh; Keller, Marc S.; Cahill, Anne Marie (Pediatric radiology, 2017)
Background Reduced-dose C-arm computed tomography (CT) uses flat-panel detectors to acquire real-time 3-D images in the interventional radiology suite to assist with anatomical localization and procedure planning. Objective To describe dose-reduction techniques for C-arm CT at a pediatric institution and to provide guidance for implementation. Materials and methods We conducted a 5-year retrospective study on procedures using an institution-specific reduced-dose protocol: 5 or 8 s Dyna Rotation, 248/396 projection images/acquisition and 0.1–0.17 μGy/projection dose at the detector with 0.3/0.6/0.9-mm copper (Cu) filtration. We categorized cases by procedure type and average patient age and calculated C-arm CT and total dose area product (DAP). Results Two hundred twenty-two C-arm CT-guided procedures were performed with a dose-reduction protocol. The most common procedures were temporomandibular and sacroiliac joint injections (48.6%) and sclerotherapy (34.2%). C-arm CT was utilized in cases of difficult percutaneous access in less common applications such as cecostomy and gastrostomy placement, foreign body retrieval and thoracentesis. C-arm CT accounted for between 9.9% and 80.7% of the total procedural DAP. Conclusion Dose-reducing techniques can preserve image quality for intervention while reducing radiation exposure to the child. This technology has multiple applications within pediatric interventional radiology and can be considered as an adjunctive imaging tool in a variety of procedures, particularly when percutaneous access is challenging despite routine fluoroscopic or ultrasound guidance.